Morfologi dan Produktivitas Kacang Hijau (Vigna radiata L.) pada Cekaman Kekeringan dengan Aplikasi Silika - Musliadi, Musliadi; Hasanah, Yaya; Hanafiah, Diana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Elnino and lanina have led to lower mung bean production and higher risk for farmers. Mung beans are one of the commodities whose export value has increased in recent years, so the problem of global warming is a serious threat that can reduce mung bean production. The purpose of this research was to determine the effect of silica application on morphology and yield of mung bean under drought stress.This research was conducted in a plastic house in Glumpang Sulu Timur Village, Dewantara District, North Aceh Regency, Aceh in February-May 2023. The research used a Randomized Block Design with two factors and three replications. The first factor was drought stress with 3 levels: 80%, 60%, 40%KL. The second factor is silica application with 4 levels: 0.15, 30, 45ml/l. The results showed that A3 drought stress (40% KL) can reduce the growth of plant height, number of leaves, leaf area, number of effective root nodules, root volume, root dry weight, crown dry weight, number of productive branches. Drought stress A3 (40% KL) also increased root length and accelerated flowering and harvesting age. Application of silica dose of 45ml/l can increase the growth and yield of mung beans. The interaction (A1S3) between 80% KL drought stress and 45ml/l silica can increase the number of mung bean seeds.